Bottom-up innovation for health management capacity development: a qualitative case study in a South African health district - Marsha Orgill; Bruno Marchal; Maylene Shung-King; Lwazikazi Sikuza; Lucy Gilson (BMC, 2021)
Abstract Background As part of health system strengthening in South Africa (2012-2017) a new district health manager, taking a bottom-up approach, developed a suite of innovations to improve the processes of monthly district management team meetings, and the practices of managers and NGO partners attending them. Understanding capacity as a property of the health system rather than only of individuals, the research explored the mechanisms triggered in context to produce outputs, including the initial sensemaking by the district manager, the subsequent sensegiving and sensemaking in the team and how these homegrown innovations interacted with existing social processes and norms within the system. Methods We conducted a realist evaluation, adopting the case study design, over a two-year period (2013-2015) in the district of focus. The initial programme theory was developed from 10 senior manager interviews and a literature review. To understand the processes and mechanisms triggered in the local context and identify outputs, we conducted 15 interviews with managers in the management team and seven with non-state actors. These were supplemented by researcher notes based on time spent in the district. Thematic analysis was conducted using the Context-Mechanism-Outcome configuration alongside theoretical constructs. Results The new district manager drew on systems thinking, tacit and experiential knowledge to design bottom-up innovations. Capacity was triggered through micro-practices of sensemaking and sensegiving which included using sticks (positional authority, enforcement of policies, over-coding), intentionally providing justifications for change and setting the scene (a new agenda, distributed leadership). These micro-practices in themselves, and by managers engaging with them, triggered a generative process of buy-in and motivation which influenced managers and partners to participate in new practices within a routine meeting. Conclusion District managers are well placed to design local capacity development innovations and must draw on systems thinking, tacit and experiential knowledge to enable relevant 'bottom-up' capacity development in district health systems. By drawing on soft skills and the policy resources (hardware) of the system they can influence motivation and buy-in to improve management practices. From a systems perspective, we argue that capacity development can be conceived of as part of the daily activity of managing within routine spaces.